An Interview Study of Social and Psychological Effects Upon Students in Malaysia and England - Ramlan, Muhammad Nadzif (ARISTO, 2022)
This study aims to explore the psychological and social effects of social media upon students at higher learning institutions in Malaysia and The United Kingdom.The study is done via qualitative approach as this study focuses on a case study to acquire unique experience by the participants.Three students are from Malaysia with and the remaining two are from England with different educational degree backgrounds.The participants mention the effects, the factors causing them and the suggestions to avoid or reduce the impacts.The finding elucidates the positive psychological effects include stimulating their study and relieving stress whereas the adverse impacts are procrastination, addiction and low self-esteem.The positive social effects mentioned by participants are student-student bonding as well as sharing of beneficial contents.The negative social effects are misinformation, cyberbullying, morality issues including pornography and cybercrimes, and poor physical interactions. The interviewees suggested that the factors that cause the negative impacts of social media were due to lockdown, peer pressure, perfectionism, procrastination and unethical usage of the online communication platforms.The research concludes with the suggestions by interviewees to impede the influence of social media in which they are parallel with previous findings of other researches such as limiting time for social media and encouraging face-to-face interaction instead.However, there are also additional inputs that are exclusively acquired due to COVID-19 and this will be elaborated further in this paper